Analysis of factors affecting the level of the human development index (Lighthouse Publishing, 2022)
Indonesia Human Development Index is included in the category of a high level of human development, but there are still disparities in human development between regions especially in Eastern Indonesia. This study uses secondary data and purposive sampling with 156 districts and cities as the number of samples that meet the criteria to determine the impact of poverty level, economic growth, education function expenditure, health function expenditure, and capital expenditure on the HDI in districts and cities in Eastern Indonesia from 2015 to 2018. Multiple linear regression is the approach of data analysis used in this study. According to the results of statistical analyses of 156 districts and cities in Eastern Indonesia, Poverty level has a negative and significant impact on HDI, economic growth has no effect on HDI, health function expenditures have a negative effect on HDI, education function expenditures have a positive effect on HDI, and capital expenditures have no effect on HDI. The results of this study can be used to provide input for regional development policy makers in the context of improving regional governance and as material for evaluating the implementation of ongoing development, as well as material for planning future strategies for decision making, especially in relation to human development. The limitation of this study is that it only uses a limited sample from 2015-2018. It is suggested for further research to add other independent variables that may influence HDI, such as the unemployment rate, minimum wage, and regional income. In addition, it is also recommended to add years of research to see the long-term effect of research results.